BUDDHIST SOCIETY AND NATIONALITY - Angela, Shelfia; Kabri, Kabri; Suyati, Suyati; Wiradharma, Bayu (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2024)
This study discusses the role of Buddhism in strengthening national insight and national unity in Indonesia, focusing on the contribution of Buddhist values ​​such as wisdom, compassion, and tolerance in the context of a pluralistic society. This study finds how Buddhist teachings, including the principles of peace and non-violence, can support the values ​​of Pancasila and build a harmonious social life. This study was conducted by analyzing the literature. The results show that Buddhists in Indonesia have the ability to increase social cohesion by participating in social and political activities that promote diversity and humanity. Buddhist teachings can help guide just and peaceful leadership behavior by implementing principles such as Dasa Raja Dhamma and Dhammavijaya. This study shows that Buddhist teachings can serve as a moral foundation to strengthen the Unitary State of the Republic of Indonesia (NKRI) by building character and actively participating in society.